Open versus Closed Polyaromatic Nanocavity: Enhanced Host Abilities toward Large Dyes and Pigments. Issue 17 (22nd February 2019) - Tsutsui, Takahiro; Kusaba, Shunsuke; Yamashina, Masahiro; Akita, Munetaka; Yoshizawa, Michito
Abstract: Host functions of polyaromatic nanocavities were revealed by using an M2 L4 molecular cage and capsule. On the basis of the previously reported M2 L4 capsule with a closed polyaromatic cavity, a new M2 L4 cage (as a mixture of the isomers) was prepared by the quantitative assembly of two metal ions and four desymmetrized bispyridine ligands with a single polyaromatic panel. The obtained, open nanocavity of the cage exhibited enhanced binding abilities toward large dyes and pigments in water. For example, two molecules of coumarin dyes were bound in the nanocavity and showed strong whitish emission (up to Φ F =34 %). Furthermore, metallopigments, the sizes of which are larger than the inner cavities of the cage and capsule, were bound only in the open polyaromatic nanocavity of the cage to give water‐soluble 1:1 host–guest complexes. Abstract : A new M2 L4 polyaromatic cage was quantitatively formed from metal ions and desymmetrized bispyridine ligands with a single polyaromatic panel. The obtained, open nanocavity of the cage exhibited enhanced binding abilities toward large organic dyes in water. Furthermore, metallopigments, the sizes of which are larger than the inner cavities of the cage and an M2 L4 polyaromatic capsule, were bound only in the open polyaromatic nanocavity of the cage to give water‐soluble 1:1 host–guest complexes.